2007
DOI: 10.1007/s11064-007-9428-4
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Time Related Oxidative Action of Hyperbaric Oxygen in Rat Brain

Abstract: Hyperbaric oxygen (HBO) is known to cause oxidative stress in several organs and tissues. Due to its high rate of blood flow and oxygen consumption, the brain is one of the most sensitive organs to this effect. The present study was performed to elucidate the relation of HBO exposure time to its oxidative effects in rats' brain cortex tissue. For this purpose, 49 rats were randomly divided into five groups. Except the control group, study groups were subjected to three atmospheres HBO for 30, 60, 90, and 120 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…In addition, Ay et al [4] also reported in another study that the oxidative effect of 2 h of HBO exposure declines to physiological levels within 90 min at most for erythrocytes and in lung tissue in rats. Korkmaz et al [40]. MDA and SOD levels were found to increase in a timedependent HBO exposure, but GSH-Px activity reflected an inconsistent course in rat brain.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, Ay et al [4] also reported in another study that the oxidative effect of 2 h of HBO exposure declines to physiological levels within 90 min at most for erythrocytes and in lung tissue in rats. Korkmaz et al [40]. MDA and SOD levels were found to increase in a timedependent HBO exposure, but GSH-Px activity reflected an inconsistent course in rat brain.…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that HBO stimulates or upregulates some biological processes such as angiogenesis, collagen synthesis, leukocyte adhesion, erythropoietin, and release of vascular endothelial growth factor (VGEF), which provide tissue healing [8,9,26]. Hyperbaric oxygen is also known for producing oxidative stress in an appropriate exposure pressure and duration-dependent manner [27,28], and it is suggested that this oxidative stress may be another of its beneficial mechanisms via stimulating antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The animal brain is often said to be especially sensitive to oxidative damage [5]. This may be attributed to its high oxygen consumption, the large quantities of oxidizable lipids and metals, and the comparatively less antioxidant mechanisms [6,7].…”
Section: Introductionmentioning
confidence: 99%